Islamic leadership and other external factors in improving the career path of lecturers - Rovian, Ivan; Widati, Sri (Universitas Negeri Surabaya, 2024)
The previous research studies conducted in East Java stated that there is a tendency for University lecturers to improve their career paths, especially those who have lecturer certification, due to the influence of lecturer behaviour, lecturer personal problems, lack of institutional facilities and information systems, and less supportive technology. This research concerns the creation of excellent quality and professional human resources. This study examines the impact of Islamic leadership encouragement, peer encouragement, availability of facilities, organizational policies, type of university, and demographic factors on lecturers' career paths. The research method uses quantitative SPSS with 345 respondents from five universities in East Java. Results showed that Islamic leadership encouragement, availability of facilities, organizational policies, type of university, and age were significant factors in improving lecturers' career paths. In contrast, gender factors did not significantly influence lecturers' career paths. This research brings some implications for University regulators and leaders regarding treatments that could be pushed to improve lecturer career paths in East Java Province.